Clinical outcomes of Arthroscopic Partial Mensisectomy for Chronic Mensical Tears in Early Post Operative Period - Muhammad Bilal Tahir; William Gaine (Medical Journal of South Punjab, 2025)
Objective: To evaluate the clinical outcome of arthroscopic partial meniscectomy in patients with chronic meniscal tears in early postoperative period. Methodology: Study was retrospective that was carried out in Orthopaedic department of Sligo university hospital from January 2020 to March 2021. Study was started after ethical approval from hospital committee. Main variables of study were discharge status, knee score preoperative, at 6 weeks and 12 weeks duration. SPSS version 23 was used for data analysis. Results: The mean preoperative knee score of the patients was 49.46±5.59. While, the mean knee score after 6 and 12 weeks of operation was gradually increase, (p=0.000). The mean knee score of male and female were almost equal, (p=0.173). Mean knee score at different age groups were also almost equal, (p=0.329). The mean knee score of lateral group was higher than medial group after 6 and 12 weeks of operation, (p<0.001). Conclusion: Arthroscopic partial meniscectomy is an effective surgical procedure for chronic or irreparable meniscal tears. Procedure improves the knee function in very short period of time after surgery as proved by improvement in WOMET knee score.